Just the nicest couple [compact disc, unabridged] - Kubica, Mary (Harlequin Audio, 2023)
Two couples are close friends until Nina's husband goes missing. Should Nina's best friend reveal having been the last one to see him? Shocking lies, betrayals, and deep secrets may soon surface.